Treatment With Reduced-Dose Trimethoprim-Sulfamethoxazole Is Effective in Mild to Moderate Pneumocystis jirovecii Pneumonia in Patients With Hematologic Malignancies. (20th May 2022) - Hammarström, Helena; Krifors, Anders; Athlin, Simon; Friman, Vanda; Golestani, Karan; Hällgren, Anita; Otto, Gisela; Oweling, Sara; Pauksens, Karlis; Kinch, Amelie; Blennow, Ola
Abstract: Background: Recent studies have reported that reduced-dose trimethoprim-sulfamethoxazole (TMP-SMX) may be effective in the treatment of Pneumocystis jirovecii pneumonia (PJP), but data are lacking for patients with hematologic malignancies. Methods: This retrospective study included all adult hematologic patients with PJP between 2013 and 2017 at 6 Swedish university hospitals. Treatment with 7.5–15 mg TMP/kg/day (reduced dose) was compared with >15–20 mg TMP/kg/day (standard dose), after correction for renal function. The primary outcome was the change in respiratory function (Δpartial pressure of oxygen [PaO2 ]/fraction of inspired oxygen [FiO2 ]) between baseline and day 8. Secondary outcomes were clinical failure and/or death at day 8 and death at day 30. Results: Of a total of 113 included patients, 80 patients received reduced dose and 33 patients received standard dose. The overall 30-day mortality in the whole cohort was 14%. There were no clinically relevant differences in ΔPaO2 /FiO2 at day 8 between the treatment groups, either before or after controlling for potential confounders in an adjusted regression model (−13.6 mm Hg [95% confidence interval CI, −56.7 to 29.5 mm Hg] and −9.4 mm Hg [95% CI, −50.5 to 31.7 mm Hg], respectively). Clinical failure and/or death at day 8 and 30-day mortality did not differ significantly between the groups (18% vs 21% and 14% vs 15%, respectively). Among patients with mild to moderate pneumonia, defined as PaO2 /FiO2 >200 mm Hg, all 44 patients receiving the reduced dose were alive at day 30. Conclusions: In this cohort of 113 patients with hematologic malignancies, reduced-dose TMP-SMX was effective and safe for treating mild to moderate PJP. Abstract : In a cohort of 113 patients with hematologic malignancies and Pneumocystis jirovecii pneumonia, treatment with reduced-dose trimethoprim-sulfamethoxazole was as effective as standard-dose treatment in patients with mild to moderate pneumonia.